Why Japanese? Why Not Japanese? : A Case Study of Chinese International Students Studying Japanese at American Universities - Xu, Jun (Journal of International Students, 2020)
As Chinese students have become a larger share of the international student population at U.S. universities, their participation in Japanese language classes has increased. However, Chinese student enrollment significantly decreases after the completion of the first Japanese class, and consequently, fewer Chinese students take intermediate or advanced level classes. This study examined the experiences of Chinese international students enrolled in Japanese classes as well as those who stopped taking Japanese after the first quarter or first-year class in a private university in the United States. We used semistructured interviews to investigate the reasons and goals of Chinese international students for studying the Japanese language, the successes or challenges both inside and outside of the Japanese classroom, and the reasons students continue or discontinue learning Japanese.